Evaluation of clinical outcome of thrombolytic therapy in elderly patients in Western Rajasthan: a single centre experience - Mathur, Rohit; Yadav, Palsingh; Sanghvi, Sanjeev; Sarda, Pawan; Baroopal, Anil; Mahajan, Swati (International Journal of Research in Medical Sciences, 2019)
Background: Heart disease is the leading cause of mortality in population above the age of 65 years. Severity and prevalence of coronary artery disease (CAD) increase with increasing age. Thrombolysis remains the standard of care in the management of acute ST-elevation myocardial infarction (STEMI) in developing countries like India where primary percutaneous coronary intervention (PCI) is still not possible in the majority of patients. The risks and benefits of thrombolytic reperfusion therapy among the elderly patients with STEMI is much less known. Authors aimed to evaluate the outcome and complications of thrombolytic therapy in elderly patients admitted with acute STEMI. Methods: The present observational study was done between January 2017 and January 2019 in the department of cardiology, Dr. S.N. Medical College, Jodhpur, India. It included a study group comprising 102 consecutive elderly patients who had acute STEMI and underwent thrombolytic therapy and a control group comprising 102 consecutive elderly patients who had STEMI who were not given thrombolytic therapy. Both groups were evaluated for an outcome (in-hospital mortality) and complications. Results: The overall in-hospital mortality was less in thrombolytic therapy group as compared to control group although not statistically significant (8.82% versus 14.70%, p=0.277). Similarly, in-hospital mortality was less in thrombolytic therapy subgroup A (age 66-74 years) as compared to control subgroup A (6.45% versus 10.75%, p=0.583) and also less in thrombolytic therapy subgroup B (age 75-85years) as compared to control subgroup B (12.50% versus 21.62%, p=0.445). Among the traditional risk factors, co-morbid conditions and complications, there was less prevalence of diabetes mellitus (4.90% versus 15.68%, p=0.021), hypertension (5.88% versus 6.86%, p=1.000), cardiogenic shock (8.82% versus 9.80%, p=1.000), left ventricular failure (LVF) (0.98% versus 3.92%, p=0.365) and atrioventricular (AV) block (0% versus 4.90%, p=0.245) but more acute kidney injury (AKI) (2.94% versus 0%, p=0.070) in thrombolytic therapy group patients as compared to control group patients. Cerebrovascular accident (CVA) did not occur in both group patients. Conclusion: Despite the higher prevalence of co-morbidities and high risk features in elderly patients of acute STEMI, timely thrombolysis is beneficial. A mortality benefit was seen in all groups suggesting net benefit regardless of increasing age up to the age of 85 years.